A Sulfur K-Edge XANES and Raman Study on the Effect of Chloride Ion on Bacterial and Chemical Leaching of Chalcopyrite at 25 °C Mining, Metallurgy and Exploration - Xiyu Gao; Yi Yang; Mark I. Pownceby; Shuiping Zhong; Miao Chen (Society for Mining, Metallurgy & Exploration)
In the present study, X-ray diffraction (XRD), scanning electron microscopy (SEM), X-ray absorption near edge structure (XANES) spectroscopy, and Raman spectroscopy were used to investigate the effect of chloride ions on chalcopyrite bioleaching and chemical leaching at 25 °C. The leaching results show that the addition of chloride ions suppressed the dissolution of chalcopyrite in both chemical and bacterial leaching. In chemical leaching, the solution redox potential in the experiment without Cl− stayed in a range more suitable for chalcopyrite dissolution compared with experiments with Cl− . In bioleaching, the bacteria activity was suppressed by Cl− leading to low dissolution rates of Cu. Surface morphology and chemical speciation studies confirmed the formation of potassium jarosite on the surface of the chalcopyrite leach residues. In addition, S K-edge XANES indicated the formation of trace amount of elemental sulfur and covellite on the mineral surfaces.